Fatigue behavior and morphology in selective laser melted Ti-6Al-4V cellular materials (Transactions on Additive Manufacturing Meets Medicine, 2019)
Selective Laser Melting (SLM) has shown great potentialities in the production of lattice materials due to the intrinsic advantages of rapid prototyping technologies. Nevertheless, the low accuracy and precision of this manufacturing process is a well-known issue that is critically important for the fatigue properties of metallic lattices with strut thicknesses of a few hundred microns. In this work, we discuss some aspects regarding the relationship between the as-built morphology of SLM Ti-6Al-4V cubic cell lattice structures and their fatigue properties.
Keywords: Selective Laser